Death following extreme temperature exposure: Histological, biochemical and immunohistochemical markers. (January 2021) - Natanti, Alice; Mazzanti, Roberta; Palpacelli, Marco; Turchi, Chiara; Tagliabracci, Adriano; Pesaresi, Mauro
Introduction: Defining extreme temperatures as the cause of death remains challenging. It is mostly based on circumstantial, macroscopic and microscopic features. Methods: We retrospectively compared groups of cases of fatal hypothermia, fatal hyperthermia and non-extreme temperature-related deaths. We analysed specific histological findings, focusing on samples from the liver, pancreas and kidney. Results: Between 1 January 2013 and 31 December 2016, 15 autopsies were performed for deaths related to extreme temperatures. They included 11 cases of fatal hypothermia (group A), four cases of fatal hyperthermia (group B) and eight controls (group C). Perinuclear hepatocyte vacuolisation was observed in seven cases of hypothermia, one case of hyperthermia and four controls. Pancreatic cytoarchitecture was well preserved in two cases of hypothermia, one case of hyperthermia and two controls. No particular microscopic feature was found in pancreatic samples. Renal epithelial tubular cell vacuolisation was observed in seven cases of hypothermia and one case of hyperthermia, while it was absent in all controls. Chromogranin A (CgA) was markedly positive in the pancreatic tissue of five cases of fatal hypothermia and one control, and mildly positive in one case of fatal hyperthermia. No significant p -values were observed for any comparisons ( p > 0.05), except when hypothermia cases group were compared to the control group for the Armanni–Ebstein phenomenon test ( p = 0.0078). Conclusions: Although our study did not find a specific microscopic marker, hepatocyte vacuolisation, the Armanni–Ebstein phenomenon and pancreatic CgA positivity, taken together, may be useful tools to confirm hypo- and hyperthermia-related deaths, in addition to circumstantial and macroscopic findings.